Sosialisasi dan Deteksi Dini Diabetes Mellitus sebagai Upaya Pencegahan Komplikasi di Woha Kabupaten Bima - Indra Rahmad; Julhana; Hendari, Rini (Jurnal Pengabdian Masyarakat Cendikia Jenius, 2024)
Early detection of type II diabetes mellitus can be performed through self-monitoring of blood glucose or at the nearest healthcare facility. This activity aims to increase the motivation and knowledge of the community regarding early detection of diabetes mellitus and prevention of complications. The activity was conducted in Rabakodo Village, Woha District, in May 2024. The method used involved a pre-test to assess initial knowledge, followed by lectures, discussions, and a post-test. Based on respondent characteristics, the majority of diabetes patients were aged 46-65 years, with 68% being female and 72% having a high school education, while 24% had only attended junior high school. Before the counseling, 64% of the community at the Woha Health Center had sufficient knowledge about early detection of diabetes, and 36% had limited knowledge. After the counseling, the results showed a significant improvement, with 80% of the community having good knowledge and 20% having sufficient knowledge. Conclusion: The counseling successfully improved the community's knowledge about early detection of diabetes, with 80% having good knowledge.